Postoperative Management of Patients with Articular Cartilage Repair - Stone, Jennifer Yasu; Schaal, Robert (The Journal of Knee Surgery, 2012)
The efficacy of the rehabilitative process following articular cartilage repair in the knee can be the factor that determines the patient's long-term success, especially for return to sport. Articular cartilage repairs show great promise in allowing patients to return to their former level of function and, when complimented with an appropriate postoperative rehabilitation program, can be highly successful in allowing return to even very high level athletics. This article seeks to overview the most recent evidence regarding the general rehabilitation process for the common types of cartilage repair, discuss common complications which may arise, and determine an athlete's readiness to return to sport. We also address postoperative pain control, evaluation of a patient's progress through rehab, and adjustments to be made when there are comorbidities present.
Keywords: articular cartilage; rehabilitation; physical therapy; postoperative